The origin of TeV electrons in blazars - Kazanas, Demosthenes; Mastichiadis, Apostolos (1999)
There is increasing observational evidence that relativistic particles of energies ∼1 TeV provide a significant pressure component of the plasma which powers at least some of the relativistic jets associated with AGN. Furthermore, observations of flares with duration ∼15 min at TeV energies indicate that the associated electrons are accelerated to the required energies on these or shorter time scales, which are comparable to the synchrotron loss time for the values of the magnetic fields thought present in these jets. As such, they push the potential acceleration mechanisms to their limits and prompt us to examine the conditions under which it may be possible for hadronic processes to provide the electrons of the requisite energies. Relativistic hadrons could presumably exist within the flow, having been accelerated efficiently near the compact object and then transported along with it, releasing their energy by an instability due to p- γ reactions once a well-defined threshold is reached.